Who moved the textbook ...? A case study describing how ideological change in South Africa manifested itself in terms of racial representation in a transitional Afrikaans language textbook series - Ebersohn, L. (Liesel) (University of Pretoria, 2013)
Dissertation (MEd (Educational Psychology))--University of Pretoria, 2006.